PENGARUH KOMPENSASI, GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PT. PLN UNIT PELAKSANA PELAYANAN PELANGGAN SURAKARTA - Vanny Crismonita; Alwi Suddin; Lamidi Lamidi (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This research was conducted at PT. PLN UP3 Surakarta, the types of data used are qualitative and quantitative data. Data sources used are primary data and secondary data. The sample in this study were all employees of PT. PLN UP3 Surakarta, amounting to 35 employees. Data collection using a questionnaire while data analysis was performed using multiple linear regression analysis. In this study shows that compensation does not significantly influence the performance of employees of PT. PLN UP3 Surakarta, leadership style has a significant effect on the performance of PT. PLN UP3 Surakarta and work discipline have no significant effect on the performance of PT. PLN UP3 Surakarta.